Mighty Jack and the Goblin King - Hatke, Ben (Hatke, Ben. Mighty Jack, 2017)
Jack and Lilly follow Maddy's captor to a strange floating crossroads where they encounter rats, brutal giants, and a fearsome Goblin King.